Mortality in patients with psoriatic arthritis: a systematic review and meta-analysis - Huang, Hong; Xie, Wenhui; Geng, Yan; Fan, Yong; Zhang, Zhuoli (Frontiers in Immunology, 2025)
ObjectiveThe debate persists regarding whether patients with psoriatic arthritis (PsA) face an increased risk of mortality. We aimed to ascertain the magnitude of all-cause mortality risk in patients with PsA compared to the general population through a systematic review and meta-analysis.MethodsWe conducted a comprehensive search of PubMed, EMBASE, and the Cochrane Library for studies published from inception to June 2025. STATA meta-analysis software was used to calculate the pooled risk estimates for mortality, represented as the standardized mortality ratio (SMR).ResultsAmong the 4,502 articles identified in our research, 20 studies were included in the analysis. Overall, our findings revealed a 1.12-fold increased risk of death among patients with PsA compared to the general population (meta-SMR: 1.12, 95% CI 1.09-1.15). Subgroup analyses showed that mortality risks were elevated in Asian countries (meta-SMR: 1.28, 95% CI 1.04-1.57), in population-based studies (meta-SMR: 1.13, 95% CI 1.02-1.25), and among studies including over 1,000 patients (meta-SMR: 1.12, 95% CI 1.01-1.25). Malignancy, cardiovascular and cerebrovascular diseases, and infection/respiratory diseases emerged as the most frequent causes of mortality.ConclusionOur analysis suggested modestly elevated mortality in patients with PsA compared to the general population, though heterogeneity warrants cautious interpretation. Malignancy, cardiovascular and cerebrovascular diseases, and infection/respiratory disease were frequent causes of mortality and warrant further investigation.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42021275209.